Proteoglycans contribute to the functional integrity of the glomerular endothelial cell surface layer and are regulated in diabetic kidney disease - Alina Khramova (Nature Portfolio, 2021)
Abstract All capillary endothelia, including those of the glomeruli, have a luminal cell surface layer (ESL) consisting of glycoproteins, glycolipids, proteoglycans (PGs) and glycosaminoglycans. Previous results have demonstrated that an intact ESL is necessary for a normal filtration barrier and damage to the ESL coupled to proteinuria is seen for example in diabetic kidney disease (DKD). We used the principles of ion exchange chromatography in vivo to elute the highly negatively charged components of the ESL with a 1 M NaCl solution in rats. Ultrastructural morphology and renal function were analyzed and 17 PGs and hyaluronan were identified in the ESL. The high salt solution reduced the glomerular ESL thickness, led to albuminuria and reduced GFR. To assess the relevance of ESL in renal disease the expression of PGs in glomeruli from DKD patients in a next generation sequencing cohort was investigated. We found that seven of the homologues of the PGs identified in the ESL from rats were differently regulated in patients with DKD compared to healthy subjects. The results show that proteoglycans and glycosaminoglycans are essential components of the ESL, maintaining the permselective properties of the glomerular barrier and thus preventing proteinuria.